2009
DOI: 10.1021/jm900807w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Generation of a High Quality Lead for Transforming Growth Factor-β (TGF-β) Type I Receptor (ALK5)

Abstract: A novel class of 4-pyridinoxy-2-anilinopyridine-based TGF-beta type I receptor (also known as activin-like kinase 5 or ALK5) inhibitors is reported. The binding mode of this scaffold was successfully predicted by analyzing possible docked binding modes of literature inhibitors and novel synthetic ideas. Compounds such as 19 are potent ALK5 inhibitors with good physicochemical and pharmacokinetic properties and thus represent high quality leads for further optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…6 Continuous flow technologies allow coupling reactions to be safely performed at high temperatures and/or pressures and avoid the handling of reactive or dangerous intermediates. 6 Continuous flow technologies allow coupling reactions to be safely performed at high temperatures and/or pressures and avoid the handling of reactive or dangerous intermediates.…”
mentioning
confidence: 99%
“…6 Continuous flow technologies allow coupling reactions to be safely performed at high temperatures and/or pressures and avoid the handling of reactive or dangerous intermediates. 6 Continuous flow technologies allow coupling reactions to be safely performed at high temperatures and/or pressures and avoid the handling of reactive or dangerous intermediates.…”
mentioning
confidence: 99%
“…The plates were developed with QuantaBlu (Thermo Fisher Scientific, Loughborough, UK) using the manufacturer's recommended protocol and read on a Tecan Spectro-Fluor (Tecan, Switzerland) using excitation at 340/465-nm emission. (Goldberg et al, 2009). (B) TGFb-inducible SMAD3/4-dependent CAGA12 promoter-luciferase reporter bioassay carried out in both the absence (2) and presence (+) of exogenous addition of TGFb1 (1 ng/mL) for 8 hours.…”
Section: Synthetic Procedures For Az12601011mentioning
confidence: 99%
“…AZ12601011 2-(2-pyridinyl)-4-(1H-pyrrolo[3,2-c]pyridin-1yl)-6,7-dihydro-5H-cyclopenta[d]pyrimidine; structure previously undisclosed] and AZ12799734 [4-({4-[(2,6-dimethyl-3-pyridinyl)oxy]-2-pyridinyl}amino)benzenesulfonamide] (Goldberg et al, 2009;Anderton et al, 2011) are two selective TGFBR1 inhibitors. AZ12601011 and AZ12799734 inhibit TGFBR1 kinase activity (competition binding) with K d values of 2.9 and 740 nM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…3,[11][12][13][14][15][16][17][18][19][20] In a previous paper, we described the discovery of 1 21) (ALK5 IC 50 =2.7 nm, Smad2/3 IC 50 =8.7 nm), which was the most potent inhibitor of ALK5. Moreover, we reported that 1 inhibited Smad2 phosphorylation in mouse skin in such a way as to block the TGF-β/Smad signals after the topical application.…”
Section: Discovery Of 7-methoxy-6-[4-(4-methyl-13-thiazol-2-yl)-1h-imentioning
confidence: 99%